Interdependence of stock exchange indicators and GDP in selected Balkan countries - Živković Aleksandra (University Business Academy - Faculty of Economics and Engineering Management, Novi Sad, Serbia, 2021)
Stock markets and the level of their development have a great impact on economic growth. The purpose of this research is to empirically determine if there is interdependence between gross domestic product and (1) total turnover and (2) market capitalization in analyzed stock markets. By analyzing the ratio between total turnover and market capitalization into gross domestic product, the level of liquidity and activity of these stock markets can be determined, which enables the comparison of analyzed stock markets based on the mentioned financial indicators. This research included Zagreb, Ljubljana, Montenegro and the Bucharest stock market - in the period 2011-2019. The obtained results show that the analyzed markets are small and not developed, with a low level of activity and liquidity and they indicate the presence of interdependence between gross domestic product and the mentioned financial indicators.